2021
DOI: 10.1111/jfpp.15525
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol vapor, initial low O 2 , and high CO 2 stresses in the storage of Laetitia Plums

Abstract: The objective of this work was to evaluate the effect of treatments with ethanol vapor, and initial low O2 (ILOS) and high CO2 (IHCO2S) stresses on the ripening and maintenance of the quality of Laetitia plums, especially regarding internal browning (IB). The treatments evaluated were control, ethanol vapor (0.5 and 1.5%), ILOS (1.5 kPa), and IHCO2S (15 kPa). Respiratory and ethylene production rates, flesh firmness, titratable acidity, soluble solids, peel color, and incidence and severity of IB were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Chanjirakul et al (2007) reported that fruit storage under ethanol vapour increased the radical scavenging capacity in strawberries and blackberries. Recently, ethanol treatment, either in the form of vapour or applied as a coating material was reported to alleviate CI symptoms such as internal browning in plums (Steffens et al, 2021) and astringency in persimmon (Fathi-Najafabdi et al, 2021). Therefore, we suggest further study into the effect of different ULO regimes on fermentative metabolism and redox status of the fruit.…”
Section: Discussion 139mentioning
confidence: 99%
“…Chanjirakul et al (2007) reported that fruit storage under ethanol vapour increased the radical scavenging capacity in strawberries and blackberries. Recently, ethanol treatment, either in the form of vapour or applied as a coating material was reported to alleviate CI symptoms such as internal browning in plums (Steffens et al, 2021) and astringency in persimmon (Fathi-Najafabdi et al, 2021). Therefore, we suggest further study into the effect of different ULO regimes on fermentative metabolism and redox status of the fruit.…”
Section: Discussion 139mentioning
confidence: 99%